2010
DOI: 10.1021/la903738n
|View full text |Cite
|
Sign up to set email alerts
|

Control of Cell Surface and Functions by Layer-by-Layer Nanofilms

Abstract: Various nanometer-sized multilayers were directly prepared onto the surface of mouse L929 fibroblast cells by a layer-by-layer (LbL) assembly technique to control the cell surface microenvironment and cell functions, such as viability, morphology, and proliferation. The species of LbL nanofilms strongly affected the cell morphology and growth. Polyelectrolyte (PE) multilayers induced a round-shaped morphology of the adhered cells, although each component of the multilayers had high cytocompatibility, whereas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
100
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 49 publications
(33 reference statements)
1
100
0
Order By: Relevance
“…The nanometer-sized meshwork morphology of the FN films on the cell surface was found after 24 h of incubation, whereas the PE films showed homogeneous film morphologies on the cell surface (Figures 5h5j). 26 These nanomeshwork morphologies seemed to be similar to the fibrous structure of the natural ECM.…”
Section: Control Of Cell Surface and Functions By Nanofilms And Nanocmentioning
confidence: 77%
See 2 more Smart Citations
“…The nanometer-sized meshwork morphology of the FN films on the cell surface was found after 24 h of incubation, whereas the PE films showed homogeneous film morphologies on the cell surface (Figures 5h5j). 26 These nanomeshwork morphologies seemed to be similar to the fibrous structure of the natural ECM.…”
Section: Control Of Cell Surface and Functions By Nanofilms And Nanocmentioning
confidence: 77%
“…These results suggested that 4L-NHDF provided a more favorable environment for HUVECs than a cell culture plastic disk to induce high thermosensitivity and to suppress the inflammatory response from the substrate. Since the FNG nanofilms prepared on the cell surface did not affect cellular functions, 26 we concluded that the layered construct would be an analogous environment to natural tissues. These findings could be important for not only tissue engineering, but also for basic cell biology.…”
Section: High Cellular Properties Induced By 3d-architecturesmentioning
confidence: 90%
See 1 more Smart Citation
“…The FN-G nanofi lms, negatively charged under physiological conditions, were prepared by interaction through the collagen-binding domain of FN without a cytotoxic cationic component, and can provide high cyto-compatibility like native ECM. [ 21 ] The adhesion and proliferation properties of cells coated with the FN-G fi lms were comparable to non-coated cells ( Figure S3). We tried to perform the rapid construction of multilayered tissues using hFCs coated with FN-G nanofi lms.…”
mentioning
confidence: 84%
“…FN and DS had negative charges under physiological conditions. [55] Furthermore, we also successfully applied polyelectrolyte (PE) films, for example, FN-E-Lys and E-Lys-PSS, on the cell surfaces based on their common electrostatic interactions between the positive and negative components. To evaluate the LbL nanometer-sized film coating effects on cell functions, mouse L929 cells with and without different kinds of LbL films were used for proliferation experiments.…”
mentioning
confidence: 99%